Transnational Memory in 1960s Protest Movements: The Case of Greece - Salvanou, Emilia (Historein, 2023)
The paper will trace the intertwinement of social activism and memory activism in the case of the Greek 1960s, which resulted in the emergence of a transnational framework of memory. Drawing on cultural practices that emerged in the protest movements of the Greek sixties, it will scrutinise how they mobilised the past in terms that reframed national memory in a transnational context while integrating transnational frameworks of memory in the national context. It was a process through which a new memoryscape emerged that was aligned with the orientation of protest movements towards the shaping of a revolutionary present that would facilitate the closure of the post-civil war political regime, without abandoning familiar references to major national sites of memory.